2014
DOI: 10.12691/ijdsr-2-6a-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Severity and Associated Factors of Dental Caries in 3-6 Year Old Children – A Cross Sectional Study

Abstract: In the overall scheme of disease prevention, oral health is often overlooked. Oral health plays an important role in an individual's overall health. More than 90 percent of all systemic diseases have oral manifestations. Many diseases can be diagnosed in their early stages through an oral examination. Oral diseases and conditions may have a significant impact on general health; some poor general health conditions also may affect oral health status. The oral cavity is a portal of entry as well as the site of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Similarly in the study of Abayon M et 14 reported that moderate to severe dental caries among patients having diabetes. In the favor of this study Maj Saravanan SP et al 15 stated that out of all cases 34% were without caries 23% were with very mild caries, 28.5% were with mild caries, 10.2% were with moderate caries and only 3.5% were with severe caries.…”
Section: Discussionmentioning
confidence: 57%
“…Similarly in the study of Abayon M et 14 reported that moderate to severe dental caries among patients having diabetes. In the favor of this study Maj Saravanan SP et al 15 stated that out of all cases 34% were without caries 23% were with very mild caries, 28.5% were with mild caries, 10.2% were with moderate caries and only 3.5% were with severe caries.…”
Section: Discussionmentioning
confidence: 57%
“…ECC is a multifactorial disease. Its risk factors are also sociodemographic (such as a lower education level and lower socioeconomic status), poor dietary habits (especially the exposure to sugar), and poor hygiene (Wang 1996;Al-Hosani and Rugg-Gunn 1998;Al-Malik et al 2001;Rajab and Hamdan 2002;Kiwanuka et al 2004;Stecksen-Blicks et al 2004;Szatko et al 2004;Poutanen et al 2006;Psoter et al 2006;Tinanoff et al 2009;Christensen et al 2010;Slabšinskienė et al 2010;Turska-Szybka et al 2011;Prakash et al 2012;Maj Saravanan et al 2014;Nobile et al 2014;Watanabe et al 2014;Wulaerhan et al 2014). In the present studies, the teeth of three-year-olds grew gradually healthier, which was accompanied by a better parent awareness and healthier habits.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a better awareness of the causes of ECC, it remains a significant health problem in many countries (Çolak et al 2013). Its prevalence varies (Masiga and Holt 1993;Al-Hosani and Rugg-Gunn 1998;Al-Malik et al 2001;Rajab and Hamdan 2002;Kiwanuka et al 2004;Maj Saravanan et al 2014;Watanabe et al 2014); it is below 20% in some European Union countries in three-year-olds (Ferro et al 2007;Bardsley 2013; Dental public health epidemiology programme 2013; Morgan and Monghan 2015) and much higher in others (Henkuzena et al 2004;Szatko et al 2004;Jodkowska et al 2009;Slabšinskienė et al 2010;Begzati et al 2011;Olczak-Kowalczyk et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 However, it is still high among pre-schoolers of developing nations. [19][20][21] Numerous studies have revealed the magnitude of dental caries was reported as 43.6% in Thailand, 22 70.4% in china, 23 63.4% in India, 24 and 73% in Eastern Saudi Arabia. 25 The burden of dental caries is increasing rapidly in lowand middle-income nations, and, is particularly severe among children living in deprived communities.…”
Section: Introductionmentioning
confidence: 99%